2015
DOI: 10.1186/s12863-015-0221-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and relationship of Indian cattle inferred from microsatellite and mitochondrial DNA markers

Abstract: BackgroundIndian agriculture is an economic symbiosis of crop and livestock production with cattle as the foundation. Sadly, the population of indigenous cattle (Bos indicus) is declining (8.94 % in last decade) and needs immediate scientific management. Genetic characterization is the first step in the development of proper management strategies for preserving genetic diversity and preventing undesirable loss of alleles. Thus, in this study we investigated genetic diversity and relationship among eleven India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
9
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 40 publications
7
79
9
3
Order By: Relevance
“…The heterozygosity values observed in the current study were comparable to the values reported in indigenous cattle from Vietnam (Pham et al 2013), Cameroon (Ngono Ema et al 2014) and in India (Sharma et al 2015). High gene diversity levels are normally associated with long-term natural selection for adaptation and the historic admixture of different populations (Ojango et al 2011).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The heterozygosity values observed in the current study were comparable to the values reported in indigenous cattle from Vietnam (Pham et al 2013), Cameroon (Ngono Ema et al 2014) and in India (Sharma et al 2015). High gene diversity levels are normally associated with long-term natural selection for adaptation and the historic admixture of different populations (Ojango et al 2011).…”
Section: Discussionsupporting
confidence: 85%
“…Microsatellite markers have been widely used to evaluate the genetic diversity of indigenous cattle breeds (FAO, 2011). Genetic diversity has been investigated in a number of developing countries on breeds such as the Ankole longhorn (Ndumu et al 2008;Kugonza et al 2011) and Afrikaner cattle breeds (Pienaar et al 2014) as well as a number of indigenous cattle breeds in Mozambique (Bessa et al 2009), Cuba (Acosta et al 2013), Cameroon (Ngono-Ema et al 2014 and India (Sharma et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The study showed lower F st values using 760,139 SNPs from 777k chip among B. indicus breeds (0.066–0.093) compared to F st among B. taurus breeds (0.159) indicating comparatively less divergence among B. indicus breeds. A higher F st value (13.3%) considering a larger diverse panel of B. indicus breeds genotyped with microsatellite markers has previously been reported (Sharma et al., ). Results of PCA analysis for genotype data of 120 purebred animals using pruned 777k data having 138,451 SNPs showed that the first and second PC clearly separated the B. taurus from the B. indicus breeds (Figure a), while all four B. indicus breeds clustered together expect a few Red Sindhi animals (Figure b).…”
Section: Discussionmentioning
confidence: 65%
“…Population subdivision could be one of the possible causes for the observed heterozygosity deficit considering the fact that samples were collected from different geographical locations of the native breed tract. However, it also needs to be mentioned that much higher deviations from HWE have been reported in Brazilian (19.5 % breed × locus combina- Sharma et al, 2015).…”
Section: Test For Hardy-weinberg Equilibriummentioning
confidence: 93%